Pengaruh Implementasi Media Kuin P terhadap Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Pancasila di Sekolah Dasar - Hardiyansyah, Framz; Saleh, Moh.; Nurhalizah, Siti; Wulansari; Dwi Merdatul Jannah, Winda (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This research aims to describe critical listening skills learning strategies by using video media in Indonesian language learning at primary schools, particularly on folklore subjects. Listening skills are an important aspect of language proficiency, because through effective listening activities students can understand the information and meaning of messages delivered orally. This research uses a qualitative approach with multi-case study designs, which focuses on the use of video media to improve students' critical listening skills. The data is collected through observations, interviews and documentation, then analyzed using interactive models with the stages of data condensation, data presentation, and conclusions. The results show that before the use of video media, students' ability to listen to folk stories was still low, demonstrated by understated values. Once video media is applied to learning, there's a significant improvement in students' critical listening skills. Students become more enthusiastic, easier to understand the content of a story and able to answer questions accurately. Thus, the use of video media can be an innovative and effective learning strategy for improving critical listening skills in primary schools.